2016
DOI: 10.1111/aphw.12073
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Efficacy and Planning as Predictors of Physical Activity in the Context of Workplace Health Promotion

Abstract: Planning was confirmed as a predictor of physical activity, whereas self-efficacy was not. However, cross-lagged interrelations indicated reciprocal reactivation among self-efficacy and planning over time, suggesting beneficial effects of including strategies that foster both volitional constructs in interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 59 publications
3
23
0
Order By: Relevance
“…The more confidence individuals had in their own abilities, the more they benefitted from planning, whereas participants with low average levels of self‐efficacy did not translate their plans into action. This finding supports physical activity intervention approaches that focus on instilling confidence in one’s ability to remain active (Keller, Gellert, Knoll, Schneider, & Ernsting, 2016).…”
Section: Discussionsupporting
confidence: 74%
“…The more confidence individuals had in their own abilities, the more they benefitted from planning, whereas participants with low average levels of self‐efficacy did not translate their plans into action. This finding supports physical activity intervention approaches that focus on instilling confidence in one’s ability to remain active (Keller, Gellert, Knoll, Schneider, & Ernsting, 2016).…”
Section: Discussionsupporting
confidence: 74%
“…We found that during the follow-up, the participants in the intervention group often talked about some positive physical and psychological changes resulting from P-oPSI, as well as some next steps or actions about promoting mental health. Our study suggests that planning a health-related behavior could lead to improved self-efficacy or psychological self-help ability [47].…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have examined the barriers and motivators of worksite PA from the perspective of sociocognitive models. Keller et al ( 17 ) reported an increase in self-efficacy, planning and PA following a workplace intervention and showed that planning was consistently associated with subsequent PA. Hadgraft et al ( 18 ) suggested that strategies aimed at increasing employees' perceived control and self-efficacy over their sitting time might be helpful components of workplace interventions, although they only partially explained the variation in reduced workplace sitting.…”
Section: Introductionmentioning
confidence: 99%